Transformasi Psikologis Shinji Ikari dalam Evangelion: 3.0+1.0: Analisis Penerimaan Diri - Achmad Justin Syarifuddin; Hendrike Priventa (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2026)
This study aims to analyze the dynamics of self-acceptance in the protagonist, Shinji Ikari, in the film Evangelion: 3.0+1.0 Thrice Upon a Time. Operating within a descriptive qualitative framework, this research utilizes Sigmund Freud's psychoanalytic approach and the holistic concept of self-acceptance from humanistic psychology to examine Shinji’s internal transition from deep-seated adolescent trauma toward psychological recovery. Data were gathered through direct observation of the film, transcription of dialogues and pivotal scenes, alongside a literature review of supporting theories to identify indicators of trauma, internal conflict, and emotional dynamics experienced by Shinji. The results indicate that the main character progressively achieves self-acceptance through crucial interpersonal interactions—specifically the father-son dynamic—and conscious decision-making that marks the protagonist's emotional maturity. This study concludes that Evangelion: 3.0+1.0 Thrice Upon a Time serves not only as a narrative conclusion but also as a psychological healing space for its main character. Through Shinji's character representation, the film demonstrates that self-acceptance is the ultimate resolution to break free from the cycle of trauma and chaos.